Venous Thromboembolism Prophylaxis with Rivaroxaban in Elective Foot and Ankle Surgery. Issue 1 (19th August 2016) - Wiewiorski, Martin J.; Muheim, Leander; Huegle, Thomas; Valderrabano, Victor; Barg, Alexej
Category: Other Introduction/Purpose: Oral application for prophylaxis of venous thromboembolism (VTE) after total hip and knee arthroplasty has high acceptance among patients due to its non-invasive nature, when compared to traditional subcutaneous application of low- molecular-weight heparin (LMWH). Approximately 10% of the patients in our clinic receive oral thrombosis prophylaxis (rivaroxaban), the remaining patients receive subcutaneous prophylaxis with LMWH (dalteparin). However, no clinical data exists describing the use of oral prophylaxis in elective orthopedic foot and ankle surgery. The aims of this study where: 1. To assess the incidence of VTE after oral prophylaxis after elective foot and ankle procedures. 2. To identify risk factors for VTE after oral prophylaxis after elective foot and ankle procedures. Methods: A retrospective chart review of patients undergoing elective foot and ankle surgery between January 2010 and 2013 was performed. The type of medicamentous thrombosis prophylaxis was noted. All patients receiving oral antithrombotic medication (rivaroxaban, Xarelto©, Bayer, Germany) were included in the study. Location, length and type of surgery and tourniquet time were assessed. Co-morbidities (e.g. diabetes, coagulopathy, ASA classification) were noted. Patients previously treated with phenprocoumon or clopidrogel were excluded. A phone interview was performed and patients were asked whether a thromboembolic incident occurred or not. If an incidence was confirmed, the report of the diagnostic findings was obtained from the general practitioner. Results: 450 patients were included. Two thromboembolic incidents occurred (0.4%; deep venous thrombosis confirmed by ultrasound). Both patients had a history of previous deep venous thrombosis and a positive family history for VTE. Due to the low percentage of patients with VTE, a multivariate analysis could not be performed. Conclusion: The incidence of VTE after oral thrombosis prophylaxis with rivaroxaban is low and comparable with the incidence after subcutaneous application of LMWH.